Delimiting hyperchaotic regions in parameter planes of a 5D continuous-time dynamical system - Rech P.C.* (2014)
© 2014 Elsevier Inc. All rights reserved.Different ways to numerically characterize hyperchaotic regions in parameter planes of a 5D continuous-time nonlinear dynamical system are utilized in this work. The method considers the three largest Lyapunov exponents, to construct two-dimensional parameter planes colorful plots. In some these plots different levels of hyperchaos are represented by a continuously changing yellow to red scale, while in other different colors mean different number of positive Lyapunov exponents.